Separability of local reactivity descriptors - Tanwar, A; Pal, S (Journal of Chemical Sciences, 2005)
The size-dependence of different local reactivity descriptors of dimer A(2) and AB type of systems is discussed. We derive analytic results of these descriptors calculated using finite difference approximation. In particular, we studied Fukui functions, relative electrophilicity and relative nucleophilicity, local softness and local philicity. The results are explained using the example of the dimer of BH3NH3.
Keywords: condensed Fukai functions; Local reactivity descriptors; molecular interactions; separability

On the single-root approach within the framework of coupled-cluster theory in fock space - Horny, L; Schaefer, HF; Hubac, I; Pal, S (Chemical Physics, 2005)
A thorough formulation of Fock Space Brillouin-Wigner Coupled Cluster method is presented following previous developments [N.D.K. Petraco, L Horny, H.F. Schaefer, I. Hubac, J. Chem. Phys. 117 (2002) 9580]. The new method is designed to avoid the intruder states problem, and introduces the single-root solution feature which has not been considered yet within valence-universal methods. The explicit equations for the (0,1) sector of the Fock space are introduced. (C) 2005 Elsevier B.V. All rights reserved.